(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
There is extensive recent literature on play/dance as a physical activity that is beneficial to our physical, mental, and social wellbeing. The speakers of the symposium, movement pedagogists and therapists from three different countries, discuss the role of movement/dance in early childhood, adolescence, adulthood, and old age. Study 1 uses an embodied cognition model to understand the relationship between motor competence (MC) and executive functioning (EF) from early childhood to school age. It identifies diverse school readiness profiles in 91 children, revealing that while MC varies significantly, EF and language skills are consistently scored. The study calls for a deeper understanding of the overlap between motor, cognitive, and social skills when evaluating school readiness, as it may mitigate developmental disparities. Study 2 assesses a four-week dance-focused exergaming intervention on cognitive and psychological outcomes in adolescents, finding that while dance exposure improved working memory, psychological wellbeing changes are complex to demonstrate. Study 3 reviews 13 theses on Dance Movement Therapy (DMT), underscoring its potential in enhancing mental health and coping strategies, particularly in preventing depression. Lastly, Study 4 evaluates the preventive role of dance for neurodegenerative diseases in the elderly, with evidence showing brain volume increases and improved physical fitness in participants with cognitive impairment after dance training, highlighting dance’s contribution to neuroplasticity and overall health in older adults. The symposium emphasises the significant benefits of dance for overall health and concludes by underscoring the importance of integrating dance into programmes for diverse populations, fostering a sense of community. The audience is invited to discuss how to facilitate interdisciplinary research on pedagogical and therapeutic applications of dance related to important themes: 1. Systematic recording of the transformative health benefits of dance as an engaging form of physical activity; 2. Ways to enhance research on the relationship between dance, cognitive function, and mental wellbeing; 3. Quantitative and qualitative assessment tools applied to investigate dance interventions across health conditions; 4. The role of diverse dance styles that appeal to different age/gender/ethnic groups; 5. Creating inspiring physical activity policies and recommendations that include dance to promote healthy self-concept, body image, and reduce anxiety.